1999
DOI: 10.1038/sj.leu.2401220
|View full text |Cite
|
Sign up to set email alerts
|

Clonally unrelated BCR-ABL-negative acute myeloblastic leukemia masquerading as blast crisis after busulphan and interferon therapy for BCR-ABL-positive chronic myeloid leukemia

Abstract: We report a patient with Philadelphia (Ph)-positive, BCR-ABL rearrangement positive, chronic myeloid leukemia (CML) with a prolonged chronic phase of 24 years who was first prescribed alpha-2 interferon 22 years after initial diagnosis. This therapy was tolerated poorly on account of thrombocytopenia, but an eventual major cytogenetic response was followed soon afterwards by transformation to terminal acute myeloid leukemia (AML). Cytogenetic studies indicated that the transformed myeloblasts were karyotypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Busulfan may have worked as a causative agent in megakaryoblastic transformation in our case. The alkylating agent busulfan has been associated with clinical incidence of myelodysplasia (19), acute myeloblastic leukemia (20), increased incidence of DNA damage in mammalian cells in vitro (21) and damage to stem cell potential in cats (22).…”
Section: Discussionmentioning
confidence: 99%
“…Busulfan may have worked as a causative agent in megakaryoblastic transformation in our case. The alkylating agent busulfan has been associated with clinical incidence of myelodysplasia (19), acute myeloblastic leukemia (20), increased incidence of DNA damage in mammalian cells in vitro (21) and damage to stem cell potential in cats (22).…”
Section: Discussionmentioning
confidence: 99%
“…Fayad et al [4] suggested that the emergence of Phnegative abnormal clones in Ph-positive CML was related to the therapy or to the evolution of new clones other than the CML clone. In the reported cases, Ph-negative acute leukemia developed after the patients received busulphan, interferon, hydroxyurea, or bone marrow transplantation for CML [5][6][7][8]. Our patient was treated with interferon for 3 weeks and imatinib mesylate for 4 months.…”
Section: Discussionmentioning
confidence: 84%
“…Some authors have suggested that the selective suppression of the Ph-positive clone with CML treatment may induce an environment that allows the evolution and expansion of a new or previously silent leukemic clone, causing acute leukemia [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Fayad et al (1997)) described two cases of Ph − leukaemia (myeloproliferative disorder with 18p abnormality, and MDS with monosomy 5 and 7) after complete cytogenetic response to interferon. Manley et al (1999) reported a co‐existing Ph − leukaemic clone in a Ph + CML patient, also after complete CG response to interferon. Ph − cells with trisomy 8 had also been detected by FISH, after interferon therapy or autologous BMT (Bilhou‐Nabera et al , 1993; Ariyama et al , 1995).…”
Section: Discussionmentioning
confidence: 99%